De Re Metallica Libri XII 1556 - Agricola, Georgius; Kock, Jan (Hikuin, 2010)
Georgius Agricola: De Re Metallica Libri XII 1556 Introduction by Jan Kock The German doctor and mineralogist, Georg Bauer (Georgius Agricola) worked until his death in 1555 on the extensive publication: De Re Metallica Libri XII. The contents focus on mining and metallurgy in all its diversities, as well as glass production. He lived for years at Joakimsthal/Jáchymov on the south side of the North Bohemian Mountains, where at the time were many glass works. Within the field of glass production he informed that he had studied the subject during a stay at the »glass island« Murano near Venice. Important in this book are the 289 woodcuts showing the different production processes, such as the four concerning glass shown here. The description of the glass production is the last part of his book. The work of Agricola stayed as a reference book until the end of the 17th century. This English translation was completed in 1912 by Herbert Clark Hoover and Lou Henry Hoover and is taken from a 1950 edition, reprinted in 1986.